2017
DOI: 10.1080/15476286.2017.1349049
|View full text |Cite
|
Sign up to set email alerts
|

Functionality of tRNAs encoded in a mobile genetic element from an acidophilic bacterium

Abstract: The genome of the acidophilic, bioleaching bacterium Acidithiobacillus ferrooxidans, strain ATCC 23270, contains 95 predicted tRNA genes. Thirty-six of these genes (all 20 species) are clustered within an actively excising integrative-conjugative element (ICEAfe1). We speculated that these tRNA genes might have a role in adapting the bacterial tRNA pool to the codon usage of ICEAfe1 genes. To answer this question, we performed theoretical calculations of the global tRNA adaptation index to the entire A. ferroo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…Besides, some tRNA genes occurring in these viruses are organized in clusters comprising up to dozens of tRNA genes [ 2 , 4 , 11 , 12 , 13 , 14 , 15 , 16 ]. Interestingly, such tRNA gene organization is particularly common in mitochondrial genomes [ 17 , 18 , 19 ], but large clusters have been observed in the three domains of life ( Archaea , Bacteria and Eukarya ) [ 16 , 20 , 21 , 22 , 23 , 24 , 25 ]. Studies indicate that the presence of tRNA genes in virus genomes would be to compensate for differences in codon and/or amino acid usage between virus and hosts, favoring an efficient protein synthesis and/or expanding the host range [ 2 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, some tRNA genes occurring in these viruses are organized in clusters comprising up to dozens of tRNA genes [ 2 , 4 , 11 , 12 , 13 , 14 , 15 , 16 ]. Interestingly, such tRNA gene organization is particularly common in mitochondrial genomes [ 17 , 18 , 19 ], but large clusters have been observed in the three domains of life ( Archaea , Bacteria and Eukarya ) [ 16 , 20 , 21 , 22 , 23 , 24 , 25 ]. Studies indicate that the presence of tRNA genes in virus genomes would be to compensate for differences in codon and/or amino acid usage between virus and hosts, favoring an efficient protein synthesis and/or expanding the host range [ 2 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…We have found previously a similar trend while analyzing codon usage and tRNA gene content of an integrative conjugative element present in the genome of the chemolithoautotrophic bacterium Acidithiobacillus ferrooxidans [15,21]. Nevertheless, recent reports have shown that most tRNAs in this mobile element are expressed at very low levels [22], questioning their ability to improve gene expression. If it is common that changes in tRNA gene copy numbers produce only small changes in tRNA levels, then we would expect these have minor effects on gene expression and, consequently, on the frequency of codon usage in most genes of the genome.…”
Section: Introductionmentioning
confidence: 63%
“…who have questioned the role of tRNA gene numbers in selection of codon bias, based on the absence of correlation between the number of tRNA genes and enrichment of C vs U ending codons in the case of 4 amino acids coded by two codons translated by a single tRNA isoacceptor [28]. Probable mechanisms allowing this stability in codon usage in organisms where tRNA gene numbers vary, are silencing of acquired tRNA genes as has been observed in A. ferrooxidans [22] or regulation of either transcription or stability of tRNAs which has also been observed under a limited number of experimental conditions [29,30]. Both mechanisms are expected to occur much faster than changes in codons usage, which would require a much larger number of mutations [31].…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence indicates a new role for tRNA genes in bacterial conjugation. Alamos et al found that the acidophilic bacterium Acidithiobacillus ferrooxidans encodes 36 of its 95 tRNAs in an integrative-conjugative genetic element [13]. Indeed, Castillo et al show that the integrases encoded in the conjugative element recognize the anticodon stem loop region in the tRNA gene for active and site-specific recombination [10].…”
Section: Trna Evolution and Modification In Microorganismsmentioning
confidence: 99%